Identification of anti‐Parkinson's Disease Lead Compounds from Aspergillus ochraceus Targeting Adenosin Receptors A2A. Issue 6 (8th June 2021) - Hu, Linzhen; Tian, Shuying; Wu, Rongrong; Tong, Zhou; Jiang, Wen; Hu, Ping; Xiao, Xueyang; Zhang, Xueke; Zhou, Hui; Tong, Qingyi; Lu, Yuanyuan; Huang, Zhiyong; et al.
Abstract: Two novel alkaloids compounds together with fifteen know metabolites were identified from Aspergillus ochraceus . The stereochemistry features of the new molecules were determined via HRESIMS, NMR, ECD, and XRD analyses. Amongst these, compounds two compounds exhibited potential efficacy as anti‐Parkinson's disease with the EC50 values of 2.30 and 2.45 μM, respectively. ADMET prediction showed that these compounds owned favorable drug‐like characteristics and safe toxicity scores towards CNS drugs. Virtual screening analyses manifested that the compounds exhibited not only robust and reliable interactions to adenosine receptors A2A, but also higher binding selectivity to A2A receptors than to A1 and A3 receptors. Molecular dynamics simulation demonstrated the reliability of molecular docking results and the stability of the complexes obtained with the novel compounds and A2A receptors in natural environments. It is the first time that anti‐PD lead compounds have been identified from Aspergillus ochraceus and targeting adenosine A2A receptors. Abstract : Prenylated indole alkaloid 14 exhibited the potential efficacy towards MPP + insult SH‐SY5Y cells with the EC50 values of 2.30 μM . Virtual screening data manifested that 14 exhibited higher binding selectivity to A2A R than to A1 R and A3 R. Molecular dynamics simulation demonstrated the reliability of molecular docking results and the stability of 14 ‐A2A R complex in natural environments.